Psoriasis Types, Causes and Medication - Lima, Hermenio (IntechOpen, 2013)
By virtue of the dynamic nature of the scientific process, the description of the type, pathogenesis and treatment of a disease is always a work in progress. The complex nature of any disease can similarly be unveiled through understanding the historical context of our current understanding, examining prevailing hypotheses, and extrapolating horizons for new research. For better development of this book, the main objective was to provide insights on the types, causes, and treatments of psoriasis. This approach might substantially improve the transference of disease knowledge for physicians and intended to improve quality of medical services that endorses training of excellence and assesses the quali?cations of physicians, most of whom will be naive to clinical dermatological practices.